Column leaching test on oxidized and non-oxidized tailings in northern Norway. (October 2018) - Fu, S; Lu, J M
Abstract: Column leaching test was applied for oxide and non-oxide tailings in the Arctic area. Physico-chemical parameters (pH, pe: potential ecolotric, conductivity, TDS: Total dissolved solids, SO4 2−, salinity, Ni, Co, Zn and Mn) were measured to identified the effect of oxidized degree on heavy metals leaching from tailings. Results showed that oxidized tailings contained higher levels of Co and Ni, and their leachate was highly mineralized and less loaded with heavy metals. Non-oxidized tailings are easy to oxidation and vulcanization to generate acid drainage, weathering play more important role in oxidized tailings. Higher acid generation led to leachate having a low pH level, while strong weathering led to high levels of salinity in leachate. Acid generation and weathering controlled the release of Ni, Co, Zn, and Mn from tailings. Acid generation promotes Co and Ni release and weathering promote Mn release. Strong acid and highly salinity accelerated Co and Ni release from oxidized tailings. The source of Zn changed its origin between oxidized tailings and non-oxidized tailings leachate, with both acid mine drainage generation and weathering playing an important role in its release. Non-oxidized tailings take more sulfide that is easy to generate acid, oxidized tailing have more oxide material that lead to high minerals. Keep tailings from vulcanization and oxidation is a good way to prevent heavy metals leaching from tailings.